Evidences of Encouraging Adoption through Frontline Demonstrations (FLDs): Indian Hybrid Rice Program - Shaik N. Meera; P. Muthuraman; S. Arun Kumar (Journal of Agricultural Extension Management, 2015)
Frontline demonstrations are considered to be an effective and useful extension activity to demonstrate the latest technologies developed at research stations to the ultimate clientele, that is, farmers, in their own fields. However, extension organizations end up only in conducting the FLDs for the benefit of the farming community, but not on analyzing the results of such demonstrations to develop an extension action plan. In this paper an attempt is made to empirically establish the usefulness of FLDs on hybrid rice, linking FLDs with other development programs and macro analysis of FLDs for developing an effective commodity extension strategy. It is expected that future extension research on FLDs (demonstrations of any kind) will adopt similar methodologies for analyzing, documenting and advocating commodity based extension strategies